Fine grained bismuth sodium titanate ceramics prepared via vibro-milling method - O. Khamman (2018)
The process of fine grained bismuth sodium titanate (BNT) ceramics prepared using vibro-milling method and the effects of sintering temperatures, density, phase formation, and microstructural evolution of ceramics were studied to find the optimum processing conditions to form highly dense BNT ceramics. Micrographs of BNT ceramics sintered at 1100, 1150, and 1175 °C showed that grain size increases as the sintering temperature is increased. The dielectric constants of BNT ceramics showed higher value for smaller grain size ceramics. X-ray diffractograms of calcined BNT powders at 500-1000°C showed no change in the average particle size of BNT and found out to be 0.2-0.4 μm. The average densities of ceramics obtained from vibro-milled powders were found to be 95% of the theoretical density and were higher than that obtained from ceramics ball-milled powder.